Phyllosphere microbial community of cigar tobacco and its corresponding metabolites - Liu, Tiantian; Guo, Shiping; Wu, Chongde; Zhang, Ruina; Zhong, Qiu; Shi, Hongzhi; Zhou, Rongqing; Qin, Yanqing; Jin, Yao (Frontiers in Microbiology, 2022)
Cigar is made of a typical fermented tobacco where the microbiota inhabits within an alkaline environment. Our current understanding on cigar fermentation is far from thorough. This work employed both high-throughput sequencing and chromatography-mass spectrometric technologies to provide new scientific reference for this specific fermented system. Typical cigar samples from different regions (the Caribbeans, South America, East Asia and Southeast Asia) were investigated. The results show that Firmicutes, Actinobacteria, Proteobacteria, Ascomycota and Basidiomycota were the predominant phyla in the cigar samples. Rather than the fungal community, it was the bacterial community structures that played vital roles to differentiate the cigar from different regions: Staphylococcus was the dominant genus in the Americas; Bacillus was the dominant genus in Southeast Asia; while in East Asia, there was no dominant genus. Such differences in community structure then affected the microflora metabolism. The correlation between microbiota and metabolites revealed that Aspergillaceae, Cercospora and Staphylococcus were significantly correlated with Sclareolide; Bacillus were positively associated with isophorone. Alcaligenaceae was significantly and positively correlated with nicotine and hexadecanoic acid, methyl ester.